(untitled) (Research, Society and Development, 2022)
With the arrival of COVID-19 in Brazil in 2020, it was necessary to take actions to try to mitigate the spread of the virus, among the measures adopted was the closing of schools and consequently a stoppage in classes. In an attempt to maintain maximum social isolation, many companies used remote work, where employees worked from their homes, following this example, Emergency Remote Teaching (ERE) was implemented in the country, a model in which students were able to access classes in their homes. Later, with the advancement of vaccination in the country, hybrid teaching was adopted. However, the educational system suffered from this change as most professionals were not used to working with technology in their classes. This article deals with a research developed through semi-structured interviews with high school mathematics teachers who worked in the years 2020 and 2021 with the objective of identifying difficulties faced by mathematics teachers in the transition from the face-to-face model to the remote and hybrid models. It is possible to perceive the practically non-existent preparation that these professionals received throughout their training, their concern with student learning and the difficulty in adapting to the use of technology as a teaching tool. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001.